ANALISIS PENGARUH UBIQUITY, PERSONALIZATION, DAN INFORMATIVENESS TERHADAP USEFULNESS DAN IMPLIKASINYA TERHADAP STICKINESS OF MOBILE APPLICATION TELAAH PADA PENGGUNA MUSIC STREAMING APPLICATION - Purnamaningsih Purnamaningsih; Nosica Rizkalla (Ultima Management : Jurnal Ilmu Manajemen, 2019)
Music streaming application in Indonesia is starting to develop, which is marked by an increasing number of users. However, with the availability of many choices of application music streaming providers, which offer ease of accessing songs encourage users to exchange from one application to another briefly. This condition is certainly not favorable for application service providers. Considering one of the advantages obtained by the application provider is the purchase of paid content on the application. The longer an application has used the possibility to buy paid content, the higher. For this reason, this study aims to increase the frequency of application usage through the approach of post-adoption, namely stickiness. It is expected that users of music streaming applications can continue to use the application in the long run and take advantage of other services in the application. Four hypotheses will be tested and analyzed with structural equation model (SEM). The results showed that ubiquity and personalization affect usefulness, which in turn will increase stickiness. Whereas in this study, informativeness proved not to influence usefulness. The research implications describe efforts to increase the perception of the benefits of an application so that paid users want to use the application in the long run.